The Possibilities of Theory - the Theory of Possibilities - Woźniak-Czech, Ewelina (Przestrzenie Teorii, 2024)
This essay attempts to describe a new field of research in contemporary literary theory, defined in terms of performative, dramatic, and dramaturgical interactions and relations. The focus is placed on the dynamic movement of concepts and categories, as it allows theory to keep up with the constant new developments in literature and culture. These movements give rise to a dramatic discourse that replaces traditional methodologies. Such a transdisciplinary dialogue allows for a complex play of meanings. Any theory is a sum of choices made from among many possibilities, compatible approaches and ideas, and potential perspectives. In the new theoretical perspective described in this essay, no theory of a work of art is rejected and each remains valid, as long as it functions inclusively in a field of many different possibilities. The dramaturgy of concepts, the potential tensions and possible contradictions between them, which, paradoxically, are not mutually exclusive, complex plays and displacements, fractures and entanglements, open up new theoretical horizons. Indeed, we should ask whether the time of grand theories has passed or whether one of the most comprehensive literary theories is being created today, as it unites all past and future concepts involved in the study, interpretation, and reception of literature. It is the theory of possibilities.